COST AND EFFECTIVENESS OF OVAPRIM®, OVATIDE® AND FISH PITUITARY EXTRACT ON INDUCED SPAWNING OF AFRICAN CATFISH - EGWENOMHE, M.; OBI, A. (Nigerian Journal of Fisheries, 2012)
A single intramuscular injection of each of Ovaprim at 0.5 ml/kg, Ovatide at 0.2 ml/kg, (both synthetic hormones), and Fish Pituitary Extract (a natural hormone) given in dose unit with 1 ml normal saline/kg of recipient, was used to induce spawning in the African catfish (Clarias gariepinus) in order to determine their effectiveness and comparative cost. A control treatment received 1ml of normal saline. Results showed that there were significant differences (P < 0.05) among the three treatments in latency period and fertilization rate. However, the percentage of normal larvae was similar among the treatments indicating that the three hormonal approaches (Pituitary extract, Ovaprim and Ovatide) were equally effective for induced breeding of the African catfish. The comparative cost-effectiveness of the three hormones showed that effective dose of fresh Pituitary extract (N2,623  125) cost about three times that of Ovaprim (N952  41.5) and about nine times that of Ovatide (N300  12.4). Comparison of Ovaprim and Ovatide showed that the effective dose of Ovaprim cost more than three times as much as that of Ovatide. Ovatide, being the most cost-effective, appears preferable as the choice hormonal material for induced breeding of the African catfish (Clarias gariepinus).